Using recombinant human follicle stimulating hormone in the ovulatory infertility. - Rodríguez, Washington (2015)
OBJECTIVE: To study the effects using multiple doses of recombinant human FSH in nine women with hypogonadotropic hypogonadism, analyzing their ability to induce follicular growth and synthesis of ovarian steroids. DESIGN: Open clinical work. MATERIALS AND METHODS: Nine cases of gonadotropin hypogonadism, one had a diagnosis of Kallmann's syndrome, an isolated gonadotropin deficiency seven secondary panhypopituitarism to hypophysectomy. injections 1M hFSHR (follitropin alfa Institute Ares-Serono, Geneva) was administered in increasing doses (week 1: 75 IU / day, week 2: 150 IU / day, week 3: 225 IU / day) for an average of 17 days (range: 15-19). Blood sampling and ultra studies regularly to monitor frequent sonographic follicular development was made. For hormonal measurements was used to radioimmunoassay. RESULTS: The initial serum FSH and luteinizing hormone (LH) were 0.48 (0.9-1.22) IU / L and 0.26 (˂0.15, 0.41) IU / L, respectively. The maximum values of FSH during the test reached 10.3 (7.9-13.6) IU / L, while serum LH significantly remained stable 0.33 (0.19 to 0.52) IU / L. Serum levels of androstenedione and testosterone showed no significant changes during the administration of hFSHR and serum estradiol showed only a slight increase: 131.7 (51-239) pmol / L. Multiple pre-ovulatory follicles reached dimensions (˃ 14 mm), with a follicular development index 1.92 ± 0.7 mm / day were developed. CONCLUSIONS: From this study it appears that the hFSHR was effective in deficient women gonadotropins to stimulate normal follicular growth to the preovulatory stage and induction of ovulation, not prevent the slight increase observed estradiol. Similarly, serum levels of endogenous LH extremely low progressed with deficient androgen secretion, indicating the need for such gonadotrophin to induce an appropriate steroid synthesis.